Reference guide to anti-money laundering and combating the financing of terrorism - Schott, Paul Allan (World Bank e-Library., 2006)
This second edition of the Reference Guide is a comprehensive source of practical information on how countries can fight money laundering and terrorist financing. Aimed at helping countries understand the new international standards, it discusses the problems caused by these crimes, the specific actions countries need to take to address them, and the role international organizations play in the process. The Reference Guide is a valuable tool for establishing effective regimes to successfully prevent, detect, and prosecute money laundering and terrorist financing.